The Dynamics of Paradiplomacy Practices in the â€œFrontierâ€ Areas in Indonesia - Surwandono, Surwandono (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
In the last few decades, the practice of paradiplomacy in Indonesia has increased across the country. The paradiplomacy policy was commonly conducted by local governments in Indonesia since the collapse of the centralized-New Order regime followed by political reformation in various sectors. Decentralization is the main issue that demand local government to be more active and to manage the region properly. The opportunity to boost international partners is very open under the new norm that pave the way to the practice of paradiplomacy including in the frontier areas in Indonesia. This research focuses on the thwo important areas in the frontier Indonesia namely, Riau Island, West Kalimantan and Maluku. Nevertheless, in fact, the so-called â€œceremonialâ€ paradiplomacy blatantly practiced amid of the tighten and very bureaucratic barrier including obstacles on the budget implementation. This is qualitative research with discourse analysis which so important to understand paradiplomacy practices notably in the frontier areas in Indonesia that in some extent are vulnerable to the separatism issues in the central government in Jakarta.